Effects of different grinding levels (particle size) of soybean hull on starting pigs performance and digestibility - Moreira I. (2009)
Two experiments were carried out to study the effects of grinding of soybean hulls (SH) on starting pigs (15-30 kg) diets. Experiment I consisted of a digestibility trial with 12 barrows, initial average body weight 21.9±1.29 kg, in which the best digestibility coefficient (DC) of DM and GE was obtained with SH ground through a 2.5mm screen mesh, evaluated for CP and ME, a best DC was attained with 3.0 mm screen mesh. In the Experiment II, five diets with increasing SH (2.5 mm) levels (0, 3, 6, 9 and 12 %) for starting piglets were formulated. A quadratic response in daily weight gain (DWG) occurred, according to SH inclusion. Worst DWG occurred at 7.75 % SH inclusion. Daily feed intake, feed: gain ratio and plasma urea nitrogen were not affected by inclusion levels. In conclusion, although soybean hull grinding improves the digestible nutrients, inclusion of SH on starting pig diets is economically unfeasible.